2002
DOI: 10.1007/s11661-002-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Orientation domains and texture in hot-dipped galvanized coatings

Abstract: A. SÉ MOROZ, L. STREZOV, and M. RAPPAZThe crystallographic orientation of galvanized coatings (Zn-0.2Al-0.15Sb in wt pct) has been characterized by Electron-Backscattered Diffraction (EBSD) and optical microscopy. While 80 pct of the nucleation spots in the coating give rise to single-crystal Zn grains, it has been found that about 20 pct of them give rise to two or more orientation domains, each having a specific crystallographic orientation. For such "polycrystalline Zn grains," the orientations of the domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…Diffusion of Ti +4 ions through the ionic lattice of TiO 2 It was proven above that the rate-limiting step of TiO 2 growth is the diffusion of Ti +4 ions through the ionic lattice of TiO 2 . Then, the thickness of the TiO 2 layer is written as [30] …”
Section: Diffusion Of Ti Atoms Through the Liquid Zn Bathmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion of Ti +4 ions through the ionic lattice of TiO 2 It was proven above that the rate-limiting step of TiO 2 growth is the diffusion of Ti +4 ions through the ionic lattice of TiO 2 . Then, the thickness of the TiO 2 layer is written as [30] …”
Section: Diffusion Of Ti Atoms Through the Liquid Zn Bathmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition to obvious corrosion requirements, the interest in decorative use of colored coatings has recently increased. [10][11][12] These two fields have been combined in some patents and research papers.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Nakata [2,8] and Xu et al [9] who conducted XRD analysis at the fracture surfaces of Mg and steel side of the Mg to Zn coated steel joint for FSW and RSW respectively did not find a strong basal crystallographic texture in the Zn interlayer. Since failure occurred through the Zn interlayer and the preferential slip plane of Zn (hexagonal close-packed structure) is known to be (0 0 0 2) basal plane for plastic deformation at room temperature [17,18], texture variations could affect the tensile properties of Zn interlayer. Therefore, study of the texture on the Zn interlayer is required.…”
Section: Texture Analysismentioning
confidence: 99%
“…Textures in hexagonal metals have attracted significant interest over the years because of their widespread use [16]. Many studies have shown texture behavior of Zn coated steel [17,18]. However, the question remains unclear about the effect of the welding process on the texture behavior of Zn coating.…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, when the c-axes of the zinc grains trend to be perpendicular to the direction of the tensile stress, the plastic deformation via basal slip become less and those via non-basal slip and twinning become dominate. (0 0 0 1) fiber texture in zinc coatings prepared by hot-dip galvanizing is often detected [21,22] because the growth rate along the 1 0 1 0 direction is much faster than that along 0 0 0 1 direction during the solidification process of zinc coating [22]. As the (0 0 0 1) fiber texture in the zinc coating is strong, i.e.…”
Section: Evolution Of the Damage After The Coating Cracksmentioning
confidence: 99%